Piedade não-litúrgica - Kloppenburg, Boaventura (Revista Eclesiástica Brasileira, 2004)
Piedade não-litúrgica (ou religiosidade popular) e Liturgia, quando criteriosamente articuladas, não entram em conflito nem se repelem mutuamente. Pelo contrário, se fortalecem e enriquecem reciprocamente. É o que mostra Dom Frei Boaventura Kloppenburg, Bispo emérito de Novo Hamburgo, RS, comentando o Diretório sobre Piedade Popular e Liturgia, da Congregação para o Culto Divino e a Disciplina dos Sacramentos. O documento, com data de 17/12/01, lembra os princípios que fundamentam essa relação e dá orientações concretas no sentido de harmonizar a piedade popular e a Liturgia. Em suma, o(a) cristão(ã) piedoso(a), chamado(a) à oração comunitária, não pode esquecer-se de entrar no quarto, fechar a porta, e orar ao Pai (cf. Mt 6,6), e até orar sem cessar, como recomenda Paulo (cf. 1Ts 5,17). Abstract: Non-liturgical devotion (or popular religiosity) and Liturgy, when carefully articulated, neither conflict with nor repel one another; on the contrary, they are reciprocally strengthened and enriched. This is shown by Fray Boaventura Kloppenburg, former Bishop of Novo Hamburgo, RS, in his commentary on the DiretóriosobrePiedadePopulareLiturgia (Directory on Popular Devotion and Liturgy) of the Congregation for the Divine Cult and the Discipline of the Sacraments. The document, dated 17th December 2001, reminds us of the principles that are the foundation for this relation and gives concrete guidelines for the harmonization of popular devotion and Liturgy. In sum, the pious Christian, called to the community prayer, must not forget to enter the room, close the door, and pray to the Father (cf. Mt. 6:6) and even pray uninterruptedly, as recommended by Paul (cf. 1Ts 5:17).